2021
DOI: 10.48162/rev.39.042
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiological and biochemical parameters during the growth and development of guava fruit (Psidium guajava) grown in Vietnam

Abstract: This research examined the ripening time of guava fruit to provide a scientific basis for better harvesting and preservation of these fruits. Biochemical research methods were used to analyse changes in physiological and biochemical parameters according to the growth and development of guava fruit. The fruit took 14 weeks after anthesis to reach its maximum size in terms of length and diameter. The chlorophyll content in guava peel peaked after 10 weeks, decreasing until week 15. The content of carotenoids, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The results indicated that the major change in the chlorophyll content was found during pre-ripe to ripe transition only. Our nding was consistent with the literature Trong et al, (2021) [14]. Upregulation of the chlorophyll degrading enzymes such as peroxidase, chlorophyllase, and chlorophyll oxidase, might be attributed [15] for the decrease of the chlorophyll content of the guava peel.…”
Section: Morphological and Anatomical Alterations During Ripeningsupporting
confidence: 93%
“…The results indicated that the major change in the chlorophyll content was found during pre-ripe to ripe transition only. Our nding was consistent with the literature Trong et al, (2021) [14]. Upregulation of the chlorophyll degrading enzymes such as peroxidase, chlorophyllase, and chlorophyll oxidase, might be attributed [15] for the decrease of the chlorophyll content of the guava peel.…”
Section: Morphological and Anatomical Alterations During Ripeningsupporting
confidence: 93%
“…This could explain the high values of AA found in the analyzed fruits in comparison with the same fruits from other studies, as sunlight is more intense in the equatorial zone. On the other hand, some studies have attributed differences in AA content in fruits to their ripeness [ 52 ].…”
Section: Resultsmentioning
confidence: 99%